Multiple spinal anomalies associated with dysgenesis of the corpus callosum - Erol, F. S. (Springer London Ltd, 2012)
The coexistence of cranial and spinal anomalies in spina bifida is well known. Although combinations of such anomalies are well recognized, coexistence of six different severe anomalies is extremely uncommon. This case illustrates the association of the partial agenesis of the corpus callosum and complex spinal malformation, consisting of meningocele and dermoid sinus, associated with diastematomyelia, syringomyelia, and tethered spinal cord. Coexistence of six different anomalies is very rare. To our knowledge, no previous cases have been reported in the literature. This report is of interest showing multiple findings on brain and spinal MRI in such a patient.
Keywords: Agenesis corpus callosum; Complex spinal malformation; Dermoid sinus; Meningocele; Diastematomyelia; Syringomyelia; Tethered spinal cord